Mastering multiple complexities - a rising challenge for Swiss innovation models: Final report on the contract "Erstellung einer Studie zum Rückgang der Innovationsaktivitäten der Schweizer Unternehmen" - Franz Barjak; Dominique Foray; Martin Wörter (ETH Zurich, KOF Swiss Economic Institute, 2023)
Switzerland is one of the most competitive countries in the world. Commercially successful innovation activities are an essential part of this achievement. However, for two decades, Swiss innovation surveys have shown a significant decline in the number of R&D active companies among all companies and of the proportion of companies reporting an innovation (product or process innovation).1 The declining number of R&D active companies has also been observed in other innovative countries, such as Germany, while again in other countries, an opposite trend has been found with more companies being engaged in R&D (e.g., Finland, Netherlands) (Wörter & Spescha, 2020). Such developments require more in-depth analyses, especially for a country like Switzerland, where prosperity is strongly based on companies' innovative capacities. This overall decline is mainly a reflection on the changes in SMEs. It raises several questions which should be answered in this project.
Keywords: 330